Efficacy of using life design-based counselling for an emerging adult who had suffered parental neglect - Le Grange, C.; Maree, J. G. (South African Journal of Higher Education, 2022)
This article reports on the value of life design-based counselling for an emerging adult who had experienced parental (emotional) neglect and was now ready to embark on a career. Purposive sampling was used to select an emerging adult who had experienced parental neglect and had entered the workplace stage. Such research in South African education contexts is limited. A QUAL + quan design was used to gather and analyse the data. An intrinsic, descriptive, exploratory intervention case study involving a single individual was the basis of the research. Thematic data analysis (in combination with ATLAS.ti) was conducted to analyse the data, that is, look for themes and subthemes in the data. The intervention enhanced the participant’s career resilience and career adaptability. Exploring her life story for themes and patterns helped her gain new insight into the meaning of her experiences. The intervention enabled her to enter a new chapter in her life from a position of strength and an improved sense of self. Longitudinal studies on the long-term effects of life design-based interventions on groups of emerging adults who had experienced different kinds of parental neglect are needed to determine the longer-term value of the kind of intervention described in this article.